Brain activity during cognitive-motor tasks in older adults with cognitive frailty: a fNIRS study. - Wang, Yin-Hsiang; Yang, Yea-Ru; Yeh, Nai-Chen; Li, Pei-Yun; Wang, Ray-Yau (Frontiers in Aging Neuroscience, 2025)
Background: Cognitive frailty has recently drawn increasing attention in the context of elderly healthcare. While structural brain alterations in older adults with cognitive frailty have been previously explored, functional brain changes particularly during cognitive-motor tasks remain poorly understood. This study aimed to investigate functional brain activity during such tasks and its relationships with task performance to deepen understanding toward cognitive frailty. Methods: This cross-sectional study included cognitive frail and healthy older adults. Brain activity of bilateral prefrontal, supplementary motor area, and premotor cortex during two differently challenging cognitive-motor tasks and usual walking was measured by functional near-infrared spectroscopy. Cognitive-motor task performance, usual walking speed, physical performance, and executive function were also measured. Generalized estimating equation was used to analyze between tasks and populations. Pearson and Spearman's correlation were used to examine relationships between task performance and brain activity. Results: Older adults with cognitive frailty activated all brain regions more during both cognitive-motor tasks than usual walking (p < 0.05) as healthy control. However, neither group showed increased brain activation during the difficult task compared to the easier (p > 0.05), despite significant task performance decline (p < 0.05). In cognitive frail older adults, activity of bilateral supplementary motor area and left premotor cortex correlated negatively with performance on the difficult task (p < 0.05). Reduced performance in executive and physical functions were also noted in older adults with cognitive frailty (p < 0.05). Conclusion: This study explored possible functional brain alterations of older adults with cognitive frailty, including neural reserve, capacity limitations, and neural inefficiency. The findings possibly contribute to identification of cognitive frailty, and intervention modulating such brain alterations is warranted in future studies.